Geant4 simulation for education in medical application - Murakami, K.; Amako, K.; Jacquemier, J.; Maire, M.; Yoshida, H. (2008 IEEE Nuclear Science Symposium Conference Record, 2008)
As various technologies of radiation therapy are rapidly developed, education of radiology is an important subject in the community. Simulation is a good tool for both teaching and learning particle interaction as visualizing radiation, providing virtual experiments by simulation, and so on. The aim of our project is to provide a framework for creating courseware for education of particle interaction using the Geant4 simulation toolkit. The framework consists of three parts, contents management system for educational documents, virtual laboratory applications using Geant4, and their deployment as interactive web applications employing Ajax new web technology. In this paper, we will demonstrate harmonic combination of these components as an educational courseware and a web service, which shows how effectively Geant4 simulation can work as an educational tool.